Measuring radiologist workload: Progressing from RVUs to study ascribable times. Issue 5 (2nd August 2018) - Pitman, Alexander; Cowan, Ian A; Floyd, Richard A; Munro, Philip L
Abstract: Introduction: The need to measure reporting workload in teaching departments remains a current pertinent need. In Australia, the Pitman–Jones reporting RVUs have been in the public domain since 2003 (revised in 2009). These are expressed in arbitrary units. In New Zealand, single‐site Christchurch Hospital reporting times have been validated and placed in the public domain. Concurrently, the RANZCR has been developing a formulaic descriptor lexicon for imaging studies (the Body System Framework). There is a need to bring these three strands of work together into a common public resource. In 2015, under the auspices of the Chief Accreditation Officer, RANZCR convened the Radiologist Workload Working Group. The goal of the group was to develop a robust method of measuring radiologist workload in teaching departments in Australia and New Zealand for the RANZCR accreditation processes of teaching departments as training sites. This paper concerns itself with one aspect of the group's work, namely reaching a consensus on radiologist study ascribable times for common imaging studies. Method: The BSF examination descriptors were reduced to a smaller, generic dataset of descriptors at the expense of loss of specificity. BSF study ascribable times had been previously obtained by stopwatch observation. The dataset was harmonized with the Christchurch descriptors to ensure commonality of case mix. The two lead authors reached an approximate consensus study ascribable time for each descriptor in agreement with the BSF and Christchurch data. Specifically, the Christchurch reporting times were relied on extensively to validate the new dataset's study ascribable times. The first draft of descriptors and times was tabled at the meetings of the RANZCR Radiologist Workload Working Group, and was progressively refined by iterative consensus. Results: The output of the Radiologist Workload Working Group comprises a simplified modality‐based table of robust descriptors and 'best estimate' corresponding study ascribable times. These can be used with the extant Pitman–Jones methodology in order to estimate the reporting workload of a medical imaging teaching department in units of time. As a first for Australia and New Zealand, nuclear medicine and PET study ascribable times have been incorporated and balanced against radiology study ascribable times. Conclusion: The RANZCR 2016 study ascribable times are ready for use by the Australian and New Zealand radiologist and nuclear medicine specialist community. We hope these times will also stimulate further data collection in our two countries towards a robust, bi‐national study ascribable times database.